A Sketch of Fintech Implementation in Waqf Management (The Case of Badan Pengelola Wakaf Ar Risalah West Sumatra) - Sania Putri Alisya; Hidayatul Ihsan; Eliyanora (International ABEC, 2022)
The purpose of this research is to see as to how fintech is implemented in waqf management using a qualitative approach. The design of this research is a case study at one of nazhirs (waqf manager) in West Sumatra, that is Badan Pengelola Wakaf (BPW) Ar Risalah. Data was collected through in-depth interviews with some informants, document analysis, and website analysis. While the triangulation techniques were occupied to validate the data, the interactive model analysis techniques were used in data analysis. The results of this research show that nazhir supports the technological developments in waqf practice by creating innovative waqf portals to raise waqf funds. However, support from the waqif (donors) is still low because potential waqifs (mostly guardians of foundation students) are still reluctant to adopt the innovation of the waqf portal. Meanwhile, the waqf portal has attracted the millennial waqif although the waqf collection has not improved significantly. This is an opportunity for nazhir to more intensively promote waqf portal to the millennial generation. In terms of accountability, nazhir uses the waqf portal to disseminate the report of waqf administration.